Pharmacologic activation of estrogen receptor α increases mitochondrial function, energy expenditure, and brown adipose tissue. Issue 1 (12th October 2016) - Ponnusamy, Suriyan; Tran, Quynh T.; Harvey, Innocence; Smallwood, Heather S.; Thiyagarajan, Thirumagal; Banerjee, Souvik; Johnson, Daniel L.; Dalton, James T.; Sullivan, Ryan D.; Miller, Duane D.; Bridges, Dave; Narayanan, Ramesh
Abstract : Most satiety‐inducing obesity therapeutics, despitemodest efficacy, have safety concerns that underscore the need for effective peripherally acting drugs. An attractive therapeutic approach for obesity is to optimize/ maximize energy expenditure by increasing energy‐utilizing thermogenic brown adipose tissue. We used in vivo and in vitro models to determine the role of estrogen receptor β (ER‐β) and its ligands on adipose biology. RNA sequencing and metabolomics were used to determine the mechanism of action of ER‐β and its ligands. Estrogen receptor b (ER‐β) and its selective ligand reprogrammed preadipocytes and precursor stemcells into brown adipose tissue and increased mitochondrial respiration. An ER‐β‐selective ligand increased markers of tricarboxylic acid– dependent and–independent energybiogenesis andoxygen consumption inmicewithout a concomitant increase in physical activity or food consumption, all culminating in significantly reduced weight gain and adiposity. The antiobesity effects of ER‐β ligand were not observed in ER‐β‐knockout mice. Serum metabolite profiles of adult lean and juvenile micewere comparable, while that of adult obesemicewas distinct, indicating a possible impact of obesity on age‐dependentmetabolism. This phenotypewas partially reversed by ER‐β‐selective ligand. These data highlight a new role for ER‐β in adipose biology and its potential to be a safer alternative peripheral therapeutic target for obesity.—Ponnusamy, S., Tran, Q.T., Harvey, I., Smallwood, H. S., Thiyagarajan, T., Banerjee, S., Johnson, D. L., Dalton, J. T., Sullivan, R. D., Miller, D. D., Bridges, D., Narayanan, R. Pharmacologic activation of estrogen receptor α increases mitochondrial function, energy expenditure, and brown adipose tissue. FASEB J. 31, 266–281 (2017) www.fasebj.org